Understanding and addressing smartphone addiction: A multidisciplinary perspective - Jun Chen; Enming Zhang (Journal of Addiction Medicine and Therapeutic Science - Peertechz Publications, 2023)
The present study investigates the escalating dependency on smartphones, with tendencies toward severe addiction, thereby causing detrimental effects on both psychological and physiological well-being. The group addicted to mobile phones exhibits behavioral and neurophysiological differences compared to the non-addicted group. Non-invasive neural modulation techniques such as transcranial direct current stimulation and aerobic exercises such as HPCOSMOS exergaming (Treadmill-based, combining action control and motion perception in a Switch game)  may represent cost-effective, adaptable, and promising therapeutic approaches. That will contribute to establishing a theoretical foundation for the rehabilitation and treatment of individuals afflicted with smartphone addiction.